PENINGKATAN HASIL BELAJAR ILMU PENGETAHUAN ALAM SOSIAL (IPAS) MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DI KELAS V SD GMIM 1 WOLOAN - Loudia Tumbelaka, Sherina; Hetty J. Tumurang; Brianne E. Jo Komedien (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low learning outcomes and limited student engagement observed in the Grade V class at SD GMIM 1 Woloan regarding the Natural and Social Sciences (IPAS) subject, specifically the topic of Earth's structural layers. The primary objective was to enhance the quality of learning outcomes and active student participation through the implementation of the Problem-Based Learning (PBL) model. The study employed Classroom Action Research (CAR), adapting the Kemmis and McTaggart spiral model, which comprises four key stages: planning, implementation, observation, and reflection. The subjects of the study were all 26 students in the Grade V class at SD GMIM 1 Woloan. Data collection involved direct observation to monitor instructional activities and formative tests—administered via worksheets—to measure students' academic achievement. The results demonstrated significant improvement across each action cycle. Teacher performance in classroom management rose from 77.5% (good category) in Cycle I to 91.25% (excellent category) in Cycle II. Concurrently, the student engagement index surged from 72.7% (fair category) to 87.5% (excellent category). This improvement positively impacted learning outcomes; the average score rose from 61.92% (with a classical mastery rate of 53.84%) in Cycle I to 80.56% (with a classical mastery rate of 88.46%) in Cycle II. Based on these findings, it can be concluded that implementing the Problem-Based Learning model is effective in enhancing student engagement, motivation, and learning outcomes in IPAS at the elementary school level.